Social media and mental health - Melton, Julian (New York, NY Alexis Press, LLC, 2023)
A presentation of the main facts about social media, and research about the relationship between social media use and mental health, to examine both the positive and negative effects. Useful to anybody working in education, social care or mental health. It will also appeal to an educated general readership"--
Includes bibliographical references and index.
Keywords: Social media -- Psychological aspects; Mental Health; Social Media; Body Image -- psychology; Self-Injurious Behavior -- psychology